IoT 태그 및 소셜 메시지 기반 사물 제어 시스템 - 백승민(Seung Min Baek); 진연주(Yeon Ju Jin); 하권우(Kwon Woo Ha); 한상욱(Sang Wook Han); 정진우(Jin-Woo Jeong) (정보과학회 컴퓨팅의 실제 논문지, 2017)
Due to the rapid growth and development of Internet of Things (IoT), various devices are now accessible and controllable anytime from anywhere. However, the current IoT system requires a series of complex steps (e.g., launch an application, choose a space and thing, control the thing, etc.) to control the IoT devices; therefore, IoT suffers from a lack of efficient and intuitive methods of interacting with users. To address this problem, we propose a novel IoT control framework based on IoT tags and social messages. The proposed system provides an intuitive and efficient way to control the device based on the device ownership: 1) users can easily control the device by IoT tagging, or 2) users can send an IoT social message to the device owner to request control of the tagged device. Through the development of the prototype system, we show that the proposed system provides an efficient and intuitive way to control devices in the IoT environment. 사물 인터넷 기술의 발달로 인하여 언제 어디서든지 손쉽게 다양한 기기들의 상태를 조회하거나 제어 할 수 있는 환경으로 발전하고 있다. 그러나 현재의 IoT 관련 시스템을 이용하여 사물을 제어하려면 어플리케이션 실행, 공간 및 사물 선택, 사물 제어 등의 여러 단계에 걸친 복잡한 조작이 필요하기 때문에 손쉽고 빠르게 사물을 제어하거나 사물 제어에 대한 요청을 발송하는 부분에 여전히 많은 한계점을 가지고 있다. 본 논문에서는 보다 효율적인 사물 인터넷 제어를 위하여 IoT 태그 및 소셜 메시지 기반의 IoT 제어 프레임워크를 제안한다. 제안하는 시스템에서는 IoT 태깅을 수행한 사용자의 사물 소유권에 따라 사물을 직접 제어하거나 사물 소유주에게 IoT 메시지 전송을 통하여 간편하게 사물을 제어 할 수 있다. 본 논문에서는 프로토타입 구현을 통하여 IoT 환경에서 보다 직관적이고 효율적인 사물 제어가 가능함을 보였다.